Site-specific conjugation of single domain antibodies to liposomes enhances photosensitizer uptake and photodynamic therapy efficacy. Issue 12 (8th March 2016) - Broekgaarden, M.; van Vught, R.; Oliveira, S.; Roovers, R. C.; van Bergen en Henegouwen, P. M. P.; Pieters, R. J.; Van Gulik, T. M.; Breukink, E.; Heger, M.
Abstract : An immunotargeted drug delivery system for hydrophobic photosensitizers was developed for application in photodynamic therapy of solid tumors. Abstract : Photodynamic therapy for therapy-resistant cancers will greatly benefit from targeted delivery of tumor photosensitizing agents. In this study, a strategy for the site-specific conjugation of single domain antibodies onto liposomes containing the photosensitizer zinc phthalocyanine was developed and tested.